2018
DOI: 10.1002/sim.8034
|View full text |Cite
|
Sign up to set email alerts
|

On the efficiency of adaptive sample size design

Abstract: Adaptive sample size designs, including group sequential designs, have been used as alternatives to fixed sample size designs to achieve more robust statistical power and better trial efficiency. This work investigates the efficiency of adaptive sample size designs as compared to group sequential designs. We show that given a group sequential design, a uniformly more efficient adaptive sample size design based on the same maximum sample size and rejection boundary can be constructed. While maintaining stable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…14 Second, we focus on GSDs and CHW designs with the same number of analyses, 16,18 not allowing GSDs with many more interim analyses as approximations to CHW designs. 8,14 Third, our performance evaluation criteria 18 are based on robust or stable statistical power for a range of 𝛿 values instead of the principle solely for pointwise power superiority. 14 It is worth pointing out that, contrary to the thought that a D CHW always downweights the data collected after the interim analysis for sample size determination, a D CHW can both downweight or upweight such later collected data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Second, we focus on GSDs and CHW designs with the same number of analyses, 16,18 not allowing GSDs with many more interim analyses as approximations to CHW designs. 8,14 Third, our performance evaluation criteria 18 are based on robust or stable statistical power for a range of 𝛿 values instead of the principle solely for pointwise power superiority. 14 It is worth pointing out that, contrary to the thought that a D CHW always downweights the data collected after the interim analysis for sample size determination, a D CHW can both downweight or upweight such later collected data.…”
Section: Discussionmentioning
confidence: 99%
“…14 This view was questioned later from different angles. [15][16][17] In a recent study, Cui and Zhang 18 introduced the concepts of uniformly more efficient (UME) and approximately uniformly more efficient (AUME) SSADs with respect to an interval of the parameter. Using simulations, they showed that given 2204 CUI a GSD, a fully adaptive SSAD could be obtained that was uniformly or approximately uniformly more efficient than the GSD.…”
Section: Introductionmentioning
confidence: 99%
“…14 In such a situation, an adaptive trial design might be helpful to reduce the sample size required. 15 If this is not feasible, the laboratory confirmation of RSV infection is a minimal requirement in the prospective observational studies, as experienced in the case of cystic fibrosis, another condition at risk for severe RSV disease but not included in the standard indication. 16 In summary, our ITS analysis did not find that in Japan there was a population-level benefit in terms of reduced hospitalizations of an expanded program of palivizumab prophylaxis for children with DS without a standard indication.…”
Section: Respiratory Syncytial Virus; Lower Respiratory Infection; Hospitalization; a Quasiexperimental Study Design; Passive Immunizatiomentioning
confidence: 99%
“…5,6 With arbitrarily chosen timing and policy for sample size determination, the method provides great flexibility in sizing a clinical trial. In their subsequent works, Cui et al further developed methods for performance evaluation and comparison of different SSA designs, [10][11][12][13][14] which were critical for understanding and implementing the designs, and directly related to their solutions to the problem of design optimization. Other relevant works to mention include the methods proposed by Lehmacher and Wassmer 7 and by Shen and Fisher.…”
Section: Introductionmentioning
confidence: 99%